Review of Refocusing and Reallocation of The Local Government Budget in Handling Covid-19 in Indonesia - Antin Okfitasari; Wulan Suci Rachmadani; Samsul Rosadi; Indah Puji Lestari; Indra Hastuti (Proceeding of International Conference on Science, Health, And Technology, 2021)
The Covid 19 pandemic in Indonesia has an impact on the level of health and economic growth. In handling the Covid 19 pandemic, it is necessary to have sufficient public funds to funding and resolve the impacts that arise. The policy of refocusing and reallocating local government budgets is one of the alternative funding for handling pandemics in Indonesia. This research uses qualitative methods with case study techniques. The data used are refocusing and reallocation data from local governments in Indonesia, both provinces, cities and districts, which are derived from data from the Ministry of Home Affairs. The results of this study indicate that there are still many implementation of refocusing and budget reallocation carried out by local governments that have not been on target with the aim of handling Covid-19. The regional government has not implemented the standard Joint Decree of the Minister of Home Affairs and the Minister of Finance concerning the Acceleration of 2020 Local Government Budget Adjustments in the Context of Handling Corona Virus Disease 2019 (Covid-19), as well as Safeguarding Public Purchasing Power and the National Economy. The local government is only just making adjustments to the Local Government Budget in handling Covid-19. The target of regions that have made Local Government Budget adjustments is still not appropriate, because areas that are exposed to a lot of Covid-19 are in fact low refocusing and reallocation of the Local Government Budget, while areas that are slightly exposed to Covid-19 are refocusing and reallocation of their Local Government Budget is high.